Breaking the Glass Ceiling: Local Gender‐Based Earnings Inequality and Women's Belief in the American Dream. Issue 4 (22nd June 2015) - Newman, Benjamin J.
Abstract : This article ties together research on gender, income inequality, and political ideology, by exploring the effect of gender‐based earnings inequality on women's belief in a fundamental tenet of the "American Dream"—meritocracy. Focusing on gender‐based earnings inequality in women's local residential context, and drawing upon relative deprivation theory, this article argues that variation across local areas in the relative economic status of women should influence the ideological outlook of resident women. In contrast to relative deprivation theory, but consistent with rising expectations theory, I argue that ideological disillusionment should peak in contexts in which women's earnings fall closely behind men, and that ideological optimism should rebound in contexts in which women's earnings have achieved parity with that of men. Utilizing pooled survey data, I find strong evidence that individual women's belief in the American Dream varies according to whether local women's relative earnings indicate confrontation with or breaking of the "glass ceiling."